2014
DOI: 10.1111/jgh.12425
|View full text |Cite
|
Sign up to set email alerts
|

Schisandrin B attenuates acetaminophen‐induced hepatic injury through heat‐shock protein 27 and 70 in mice

Abstract: The hepatic cytoprotective action of Schisandrin B against acetaminophen-induced liver injury is mediated, at least in part, by the induction of HSP27 and HSP70 in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…It has been reported that the stress tolerance by HSPs shows tolerance to not only heat stress 30) , but also to oxidant stress 31) , and mechanical stress 32) . Moreover, these effects were confi rmed not only in the articular cartilage 11,12) but also in various organs such as skeletal muscles [33][34][35] , liver 36) , and blood vessels 37) . Therefore, the heat stimulus at 41°C might reduce the apoptosis of chondrocytes, which has been reported as a part of OA pathology, through the induction of HSPs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the stress tolerance by HSPs shows tolerance to not only heat stress 30) , but also to oxidant stress 31) , and mechanical stress 32) . Moreover, these effects were confi rmed not only in the articular cartilage 11,12) but also in various organs such as skeletal muscles [33][34][35] , liver 36) , and blood vessels 37) . Therefore, the heat stimulus at 41°C might reduce the apoptosis of chondrocytes, which has been reported as a part of OA pathology, through the induction of HSPs.…”
Section: Discussionmentioning
confidence: 99%
“…Schisandrin B is the most abundant dibenzocyclooctadiene derivative in extracted from the fruit of Schisandra chinensis Baill and has been used in traditional Chinese medicine to treat physiological functions disorders, especially improve cardiac [18] and injured liver [10] as well as protects neural cell from oxidative stress [8]. In addition, Schisandrin B has been reported to possess antitumor activity in various human cancers.…”
Section: Introductionmentioning
confidence: 99%
“…1A ), the major bioactive component isolated from Chinese medicine Fructus Schizandrae, is a dibenzocyclooctadiene lignan that possesses multiple biological activities. It is reported that Sch B could protect doxorubicin (DOX)-induced cardiac dysfunction 11 , attenuate acetaminophen-induced hepatic injury 12 , and also attenuate tertbutylhydroperoxide-induced cerebral toxicity 13 . Meanwhile, Sch B was identified as a potent P-gp inhibitor and could enhance DOX-induced apoptosis in cancer cells, but not in primary rat cardiomyocytes and primary human fibroblasts 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%